Comparison of fasting overnight and 6 h in diagnosing diabetic mice - Luo, Hua; Xue, Feng (Eximia, 2021)
Objectives: Diabetes mellitus has been one of the most common human diseases, causing a great number of complications, has been studied widely. Diabetic animal models are essential to understand the pathophysiological mechanisms and treatment of diabetes. This study set out to assess the different fasting times in diagnosing diabetic mice. Methods: The diabetic mice were made by injecting intraperitoneally with STZ. The intraperitoneal glucose tolerance tests were used to identify. The blood glucose was measured separately after fasting overnight and 6 h. All data were analyzed by Statistical Product and Service Solutions and P<0.05 was considered to be significant. Results: After injecting STZ, the mice appeared diabetic symptom, the IPGTTs and immunofluorescence confirmed the diabetic mice model made successfully. The fasting blood glucose after fasting 6 h was higher than fasting overnight (P<0.05), and the diagnostic accuracy of fasting for 6 hours was higher than that of fasting overnight (P<0.05). Conclusions: Fasting 6 h is more suitable for diabetes diagnosis than fasting overnight. It may be used as a criterion of fasting blood glucose in diabetic mice.